KEBIJAKAN HUKUM PIDANA DALAM PENANGGULANGAN TINDAK PIDANA PHEDOFILIA - Reha, Febby Rahmad; Firdaus, Emilda; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Children as creatures of God Almighty and social beings, from conception until birth has the right to life and independence as well as better protection of parents, family, society, nation and country. Therefore there is no man or any other party depriving the right to life and the maedeka including the the Phedofil. Phedofilia is a form of sexual disorder that perpetrators are trying to get sexual pleasure in a way that is not fair. Children who are victims are generally aged under 12 years. Besides the psychic, Phedofilia cause physical injury. But it is nothing compared to the fear, distress, stress and trauma are feared causing the child difficulty adapting to the social environment surrounding Based on this understanding, it is this thesis formulated two formulation of the problem, namely: first, how Policy Criminal Law In Response Follow Criminal Phedofilia? Secondly, whether the penalties for perpetrators of criminal acts Phedofiliasejalan with the purpose of punishment and Human Rights?Keywords: Criminal Law Policy - Crime -Phedofilia